Leukotriene D4 Upregulates Oxidized Low-Density Lipoprotein Receptor 1 and CD36 to Enhance Oxidized LDL Uptake and Phagocytosis in Macrophages Through Cysteinyl Leukotriene Receptor 1 - Pokhrel, Sabita; Gudneppanavar, Ravindra; Teegala, Lakshminarayan Reddy; Duah, Ernest; Thodeti, Charles K.; Paruchuri, Sailaja (Frontiers in Physiology, 2021)
Endothelial permeability, leukocyte attachment and unregulated oxidized LDL (oxLDL) uptake by macrophages leading to the formation of foam cells are vital in the initiation and progression of atherosclerosis. During inflammation, several inflammatory mediators regulate this process through the expression of distinct oxLDL binding cell surface receptors on macrophages. We have shown earlier that Leukotriene D4 (LTD4) promotes endothelial dysfunction, increasing endothelial permeability and enhance TNFα-mediated attachment of monocytes to endothelium, hinting its possible role in atherosclerosis. Here we analyzed the effect of Leukotriene D4 (LTD4) on macrophage function. Macrophages mainly express CysLT1R and flux calcium in response to LTD4. Further, LTD4 potentiates phagocytosis in macrophages as revealed by the uptake of zymosan particles. Notably, LTD4 augmented macrophage phagocytosis and ox-LDL uptake that is sensitive to MK-571 (MK), a CysLT1R-specific antagonist. Mechanistically, LTD4 upregulated two receptors central to foam cell formation, oxidized low-density lipoprotein receptor-1 (OLR1/LOX-1) and CD36 in a time and dose-dependent manner. Finally, LTD4 enhanced the secretion of chemokines MCP-1 and MIP1β. Our results suggest that LTD4 contributes to atherosclerosis either through driving foam cell formation or recruitment of immune cells or both. CysLT1R antagonists are safely being used in the treatment of asthma and the findings from the current study suggest that these can be re-purposed for the treatment of atherosclerosis.